Hubungan Postur Kerja, Masa Kerja Dengan Kejadian Musculoskeletal Disorders Pekerja Pengelasan Kecamatan Juwana Kabupaten Pati - Apriliyana Dwi Wahyuni; Mitoriana Porusia (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
Musculoskeletal disorders are disorders experienced by a person ranging from mild complaints to severe pain in the joints, nerves, muscles and bones due to unnatural work which has an impact on reduced efficiency and productivity. The initial implementation of this activity was carried out on 10 workers in Juwana District, Pati Regency and it was found that 4 workers experienced musculoskeletal disorders. Then this activity was carried out on 80 welding worker participants in 25 welding places in Juwana District, Pati Regency. This activity was carried out by conducting observations and interviews. The results of the observations were entered into the Rapid Entire Body Assessment (REBA) questionnaire and the interview results were entered into the Nordic Body Map (NBM) questionnaire for welding workshop workers while carrying out their work. The results show that there is a relationship between work posture and the incidence of musculoskeletal disorders, and work period and the incidence of musculoskeletal disorders. It is hoped that the measurement of work posture, length of service, and incidence of musculoskeletal disorders can be used as material for evaluation and improvement of workers and to determine the precautions that must be taken by workers so that welding workshop workers can minimize the risk of musculoskeletal disorders occurring. In conclusion, the activities have shown that there is a relationship between work posture and the incidence of musculoskeletal disorders and there is a relationship between work period and the incidence of musculoskeletal disorders. It is hoped that work station design updates can be carried out by welding workshop owners for workers and measurements of the status of musculoskeletal disorders occur again.